2021
DOI: 10.1038/s41467-021-22835-4
|View full text |Cite
|
Sign up to set email alerts
|

Expanding the chemistry of borates with functional [BO2]− anions

Abstract: More than 3900 crystalline borates, including borate minerals and synthetic inorganic borates, in addition to a wealth of industrially-important boron-containing glasses, have been discovered and characterized. Of these compounds, 99.9 % contain only the traditional triangular BO3 and tetrahedral BO4 units, which polymerize into superstructural motifs. Herein, a mixed metal K5Ba2(B10O17)2(BO2) with linear BO2 structural units was obtained, pushing the boundaries of structural diversity and providing a direct s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
88
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

6
4

Authors

Journals

citations
Cited by 140 publications
(91 citation statements)
references
References 59 publications
3
88
0
Order By: Relevance
“…It was also apparent that most borates discussed in this review are composed of traditional [BO 3 ] and [BO 4 ] units, and few borates contain fluorinated [BO 4−x F x ] tetrahedra. Recently, the discovery of linear [BO 2 ] units in K 5 Ba 2 (B 10 O 17 ) 2 (BO 2 ) provide more useful information to push the current limits of borates to a new height 587. We can imagine that the introduction of linear [BO 2 ] units in the structures of currently available B−O/F anionic framework will cause more interesting FBBs and configuration.…”
mentioning
confidence: 99%
“…It was also apparent that most borates discussed in this review are composed of traditional [BO 3 ] and [BO 4 ] units, and few borates contain fluorinated [BO 4−x F x ] tetrahedra. Recently, the discovery of linear [BO 2 ] units in K 5 Ba 2 (B 10 O 17 ) 2 (BO 2 ) provide more useful information to push the current limits of borates to a new height 587. We can imagine that the introduction of linear [BO 2 ] units in the structures of currently available B−O/F anionic framework will cause more interesting FBBs and configuration.…”
mentioning
confidence: 99%
“…4,[11][12][13][14][15][16] In around recent ten years, there are only five studies addressing chalcogenoborates containing B 12 It is well known that borates are wonderful functional materials as either electrode materials for rechargeable batteries or second-order nonlinear optical (NLO) materials in the ultraviolet (UV) region. [20][21][22][23][24][25] On the other hand, chalcogenides are the most competitive candidates for NLO materials in the middle-infrared (MIR) region. [26][27][28][29][30][31][32][33] The combination of borates and chalcogenides has also demonstrated promising NLO and special magnetic properties.…”
mentioning
confidence: 99%
“…In addition, borates containing isolated B–O/F groups usually have metal cations with strong covalence (like M = Zn, Be, Al, etc. ), in which the cations with a higher valence state can form rigid chemical bonds (M–O/F) and break the anionic framework into a 0D configuration because of their stronger coordination ability. , Among them, the low polymerization degree of isolated B m –O/F ( m < 6) groups, like [BO 2 ], [BO 3 ], [BO 4 ], [B 2 O 5 ], [B 3 O 6 ], and [B 5 O 10 ] units, is much more than that of the highly polymerized ones (∼97 vs 3%). , To date, the [B 18 O 36 ] cluster is the largest one in the anhydrous borates and is found in Sr 8 MB 18 O 36 (M = Mg, Zn, Cd) , and NaSr 7 AlB 18 O 36 series . Other highly polymerized 0D clusters B m -O/F ( m ≥ 6), like [B 6 O n ] ( n = 12, 14), [B 7 O 14 ], [B 9 O 21 ], [B 11 O 22 ], [B 12 O 24 ] units, etc., are also very limited and have only been discovered in few borates. Studies have shown that the highly polymerized B–O clusters tend to form the same and certain configurations, like [B 12 O 24 ] and [B 18 O 36 ] units, in related compounds and are all in a cyclic formation constructed by [B 3 O 7 ] and [B 3 O 8 ] branches with an end-to-end model, and both types show identical formulas and structures. ,, Of course, the discovery of such borates greatly enriched the structural chemistry of the borate system.…”
mentioning
confidence: 99%